TECHNICAL REGULATION AS A COMPONENT OF PUBLIC ADMINISTRATION - Sokolova , V. (Theory and Practice of Public Administration, 2020)
The article analyzes the approaches to the definition of the term “technical regulation”, based on the normative legal acts of the countries of the Eastern Partnership and Ukraine, and scientific researches in the sphere of technical regulation of foreign and domestic scientists.The analysis concludes that the approaches to defining this concept differ greatly, including the definition of objects and entities of technical regulation. Reasons for the denial of technical regulation in economically developed countries have been identified. The concepts and structure of the objects and subjects of technical regulation are provided.Taking into account the current trends in the field of technical regulation, a variety of technical regulation objects has been identified due to the rapid development of new technologies, materials, products and more. This, in turn, was one of the reasons for the denial of the technical regulation system both in economically developed countries and in Ukraine.The role of public administration in the field of technical regulation is substantiated. The necessity of further study and comprehensive analysis of the technical regulation system as a component of public administration is noted.